The biogeography of Elaphe sauromates (Pallas, 1814), with a description of a new rat snake species - Jablonski, Daniel; Kukushkin, Oleg V; Avcı, Aziz; Bunyatova, Sabina; Kumlutaş, Yusuf; Ilgaz, Çetin; Polyakova, Ekaterina; Shiryaev, Konstantin; Tuniyev, Boris; Jandzik, David (PeerJ, 2019)
BACKGROUND: The rat snake genus Elaphe once comprised several dozens of species distributed in temperate through tropical zones of the New and Old World. Based on molecular-genetic analyses in early 2000s, the genus was split into several separate genera, leaving only 15 Palearctic and Oriental species as its members. One of the three species also occurring in Europe is Elaphe sauromates, a robust snake from the Balkans, Anatolia, Caucasus, Ponto-Caspian steppes, and Levant that has been suspected to be composed of two or more genetically diverse populations. Here, we studied the genetic structure and morphological variation of E. sauromates, aiming to better understand its inter-population relationships and biogeography, and subsequently revise its taxonomy. METHODS: We reconstructed the phylogeography and analyzed the genetic structure of E. sauromates populations originating from most of its geographic range using both mitochondrial (COI, ND4) and nuclear (C-MOS, MC1R, PRLR, RAG1) DNA gene fragments. We employed Maximum likelihood and Bayesian inference methods for the phylogenetic tree reconstructions, supplemented with species delimitation methods, analysis of haplotype networks, and calculation of uncorrected p-distances. Morphological variation in 15 metric and 18 meristic characters was studied using parametric univariate tests as well as multivariate general linearized models. In total, we analyzed sequences originating from 63 specimens and morphological data from 95 specimens of E. sauromates sensu lato. RESULTS: The molecular phylogeny identified two clearly divergent sister lineages within E. sauromates, with both forming a lineage sister to E. quatuorlineata. The genetic distance between them (5.80-8.24% in mtDNA) is similar to the distances among several other species of the genus Elaphe. Both lineages are also moderately morphologically differentiated and, while none of the characters are exclusively diagnostic, their combination can be used for confident lineage identification. Here, following the criteria of genetic and evolutionary species concepts, we describe the lineage from eastern Anatolia and parts of the Lesser and Great Caucasus as a new species E. urartica sp. nov. DISCUSSION: Elaphe urartica sp. nov. represents a cryptic species whose ancestors presumably diverged from their common ancestor with E. sauromates around the Miocene-Pliocene boundary. The intraspecific genetic structure indicates that the recent diversity of both species has been predominantly shaped by Pleistocene climatic oscillations, with glacial refugia mainly located in the Balkans, Crimea, and/or Anatolia in E. sauromates and Anatolia and/or the Caucasus in E. urartica sp. nov.
Keywords: Anatolia; Diversification; Phylogeny; Phylogeography; Taxonomy; Evolution; Eurasia; Reptiles